Socioeconomic Conditions in Childhood and Mental Health Later in Life - Viola Angelini; Jochen O. Mierau; Laura Viluma (Global Labor Organization (GLO), 2021)
This chapter provides a narrative review of the literature relating socioeconomic circumstances early in life to mental health and well-being later in life. It starts by highlighting the various contributions focusing on associations, then moves on to the literature attempting to identify causal effects before discussing the potential mechanisms at play. The chapter closes with a view toward research questions that may inform a future research agenda and highlights some anchors for policy.
Keywords: 330